The Effect of Organic Vegetables and Fruits’ Attributes On Consumers’ Purchase Intention in Different Generations - Daengphai, Nicha; Laohavichien, Tipparat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
The objectives of this study are to investigate the influence of the attributes of organic vegetables and fruits together with purchase intention as well as consumers’ generation. In this study, the population is consumers, who are experienced in organic vegetables and fruits. The information was gathered utilizing online surveys, with 388 respondents and an 83.44 percent response rate. Multiple regression analysis was used for the statistical analysis. The findings indicate that customers are concerned about all four aspects of organic product, including healthfulness, environmental friendliness, cost, and flavor. These four attributes are positively encouraged consumers for purchasing organics product. In contrast, there is no effect between consumers’ generation to the attributes of organic product and purchase intention. According to this study, while designing a product strategy, organic vegetable and fruit business owners should take into account the four characteristics of these products to magnify purchase intention of all consumers’ generation.